Factors Contributing to Burnout and Well-Being in Physical Therapist Students. Issue 3 (12th September 2022) - Smith, Allison; Ellison, Jennifer; Bogardus, Jennifer; Gleeson, Peggy
Abstract : Introduction: Burnout is a syndrome resulting from chronic workplace stress that has not been successfully managed. Prevention and management of burnout in the doctor of physical therapy (DPT) student population may help reduce the development of burnout later in their work life. Review of Literature: Few published studies assessing burnout have been conducted with physical therapist students. In studies with medical and nursing students, individual factors that influence the development of burnout include reduced level of physical activity, reduced level of social support, not experiencing positive life events, increased fatigue, increased stress, and decreased resilience. Environmental factors that influence the development of burnout include grading scheme and perceptions of the learning environment. Subjects: Participants included 20 DPT students from across the United States. Method: A total of 522 students from a previous study who volunteered for the present grounded theory qualitative study were stratified by burnout group (burnout and nonburnout) and geographic region. Once stratified, students were randomized and then contacted through email to set up an interview time to participate in a Zoom audio interview. A total of 20 semistructured interviews were completed ranging from 20 to 40 minutes. Results: Three major themes emerged from the data, each with 3 subthemes. The major themes included burnout experience, factors that negatively affected well-being, and factors that positively affected well-being. Discussion and Conclusion: The results of this study indicate that DPT students experienced burnout as a combination of exhaustion, disengagement, and chronic overload. Factors that negatively affected well-being while in DPT school included unmanageable stress, an excessive workload, and time pressures. Factors that positively affected well-being while in DPT school included prioritizing time, support from faculty, friends, and family, and self-awareness.